If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3m + -12 = -6 Reorder the terms: -12 + 3m = -6 Solving -12 + 3m = -6 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 3m = -6 + 12 Combine like terms: -12 + 12 = 0 0 + 3m = -6 + 12 3m = -6 + 12 Combine like terms: -6 + 12 = 6 3m = 6 Divide each side by '3'. m = 2 Simplifying m = 2
| 8(v+7)-2v=38 | | -(-2y-x+2)= | | 2x^2-10x=4x | | 8(v+7)+2v=38 | | (1)3.45=3(4.42) | | -1.2+0.15x=0 | | -18p-6(5-4p)=4(p-3)-12 | | 7x^2+151x-1372=0 | | 11y-8=5y+16 | | 8w-3=5w+18 | | ln(x+2)=7-ln(x+2) | | -81=6v-13v-18 | | -5x-19=0 | | x^3-7x+6=x^2+2x-3 | | 7x^2+6=-118 | | 2x+y=31xy | | 7x^2-24x-9=0 | | 6x+2y+6x= | | 4x(-6)=4x(-5) | | -4(-6v-u)-3(3u+5v)= | | g(-4)=-4x-4 | | -2a^2+22a+121=0 | | a^2+22a+121=0 | | 8x+5=10x+23-8x | | (-3)(12)= | | x-29=19 | | 18=6(w+6)-8w | | 8x+2=1x-19 | | 5v-41=-6(v-6) | | 2m+12=-31 | | -2+2x=4+12x | | Y=-4x+340 |